Robot-based intervention program for autistic children with humanoid robot NAO: initial response in stereotyped behavior - Ismail, Luthffi Idzhar; Shamsudin, Syamimi; Yussof, Hanafiah; Hanapiah, Fazah Akhtar; Zahari, Nur Ismarrubie (Elsevier, 2012)

(untitled)
The development and research on Human-Robot Interaction (HRI) between the humanoid robot and autistic children is new and innovative. This paper presents the initial response of stereotyped behavior in HRI between Humanoid Robot NAO and children with Autism Spectrum Disorder (ASD) during the Robot-based Intervention Program (RBIP) and normal class session. The presence of stereotyped behavior in children with ASD is being evaluated during the RBIP interaction and normal class session interaction. Humanoid Robot NAO is being utilized for the interaction in RBIP. The relationship between initial response of stereotyped behavior and the intelligence level of ASD children were analyzed during two interaction set-up, which were RBIP and normal classroom interaction, from which these findings are discussed in this paper. Our focus of discussion in this research is the initial response of autistic children exhibiting stereotyped behavior in RBIP and normal classroom session.